1992
DOI: 10.1159/000168471
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long-Term Effects of Therapy with High-Dose Furosemide in Chronic Hemodialysis Patients

Abstract: The effects of daily administration of 250-2,000 mg furosemide (F) were studied in patients on hemodialysis who still had residual renal function. In a short study, 10 patients (endogenous creatinine clearance 0.6-5.3 ml/min/1.73 m2) used 1,000 mg F twice daily during 7 days, and in a long-term study 13 patients (endogenous creatinine clearance 0.7-6.8 ml/min/1.73 m2) were treated during 1 year with 250-1,000 mg F orally each day. In the short study, we observed an increase in the 24-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 11 publications
3
27
3
Order By: Relevance
“…The study was done simultaneously with investigations of the pharmacodynamic actions and adverse effects of high dose furosemide in chronic haemodialysis patients. Those results have already been published [6].…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The study was done simultaneously with investigations of the pharmacodynamic actions and adverse effects of high dose furosemide in chronic haemodialysis patients. Those results have already been published [6].…”
mentioning
confidence: 69%
“…Previous studies have demonstrated that loop diuretics in high doses are even effective in chronic haemodialysis patients with residual renal function [2][3][4][5][6]. The diuretic response in relation to the excretion of furosemide has not been determined in these patients.…”
mentioning
confidence: 99%
“…After several sessions of ultrafiltration dialysis urine output increased. The administration of 250 mg daily of furosemide was then followed by a significant increase in hand, in another study, treatment of patients on RDT with 250-1,000 mg/day of furosemide per os showed a progressive decrease in diuretic response, so that after 12 months salt and urinary excretion was not different from In conditions of severely reduced renal blood flow, a combination of dopamine (1-1.5 g/kg body weight/min) pretreatment values [48]. Thus, considering both the uncertain results and the side effects of the high dosage of and a loop diuretic is assumed to be effective in potentiating the natriuretic effect of the diuretic.…”
Section: Amiloride [Russo Et Al Unpublished Data] (Fig 1) Responsmentioning
confidence: 94%
“…The endogenous creatinine clearance continues to decrease after the start of haemodialysis, most markedly during the first 3 months of dialysis [29]. Treatment with high-dose furosemide increased urine output in these patients, but could not prevent the deterioration of the creatinine clearance [30]. A single haemodialysis session decreased the inulin clearance, but had no effect on the clearance of creatinine, because of an opposing effect on tubular secretion [31].…”
Section: Removal Of Uraemic Waste Productsmentioning
confidence: 99%